PENGGUNAAN SENSOR PADA HANDWASHER PORTABLE SEBAGAI SALAH SATU LANGKAH PENCEGAHAN COVID 19 BAGI MASYARAKAT BINAAN - Mutiara Widasari Sitopu (Universitas Negeri Medan, 2021)
During the current covid-19 pandemic, which is still widsespread today, people are requried to maintain body and environmental hygiene by diligently washing their hands regularly, avoiding crowds, reducing activities outside the home to avoid transmission of the corona virus-19. To make it easier for the fostered community to prevent transmission of the virus by diligently washing their hands, in community service activities, research institutions and community service at the medan aviation polytechnic, they provided socialization on the use of porable handwashers using sensors to make it easier and invite to target community to diligent hand washing. The target community is given socialization of knowledge about the corona virus, provides direction on how to reduce the spread of the virus so that the target community does not easily believe in hoax news that is spreading about information that has not been proven to be true. After carring out this community service activity, it is hoped that the fostered community will care more about personal hygiene by diligently washing their hands after carrying out all activities to avoid the transmission of the corona-19 virus and support the government in reducing the transmission rate of the corona -19 virus, which at that time was increasing.